Idealtipos y modelación: bases epistémicas contra verdades universalistas sobre el calentamiento climático - Antonio Arellano-Hernández (Universidad Autónoma del Estado de México, 2015)
In this text we propose to analyze the epistemic possibilities of the ideal types for use their signification in the practice of numerical climate modeling ; we will argue that the scientific concepts and particularly the models and all more the climatic models should have the epistemic status of ideal types. The plan is translate the methodological topic of ideal type into the numerical climate modeling topic to put forward a proposal that disempowers the universalistic pretentions of the cognitive coinages of contemporary science and particularly about the climatic modeling, so that laying down a scientific self-control mechanism synthesizing subjective explanations and objective validation processes becomes feasible. From these reflections, we consider it would be appropriate that the modelers and their institutions assume the climatic modeling keeping a space of scientific self-control allowing epistemological apertures instead of nomological conclusive impossible tasks about global warming.